ADAPTIVE RE-USE UNTUK REVITALISASI EKS. BANDARA KEMAYORAN, JAKARTA PUSAT - Lukas, Fernando; Sukada, Budi Adelar (Jurusan Arsitektur dan Perencanaan, 2024)
Jakarta is rich in historical memories left over from the colonial era. However, many of these buildings are now just remnants of a valuable past. Unfortunately, some of these structures have been left neglected, leading to significant deterioration over time. It's regrettable because these historical buildings hold cherished memories and meanings. Consequently, these buildings have fallen into the phenomenon of